Total Phenolic Content and Total Flavonoid Content of Crystal Guava Fruit Extract (Psidium guajava Linn. cv Kristal) - Aulia Ulmillah; Marlina Kamelia; Devi Nata Ismiati (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Crystal guava (Psidium guajava Linn. cv. Kristal) was known to contain various secondary metabolites, particularly phenolic compounds and flavonoids, which acted as bioactive components with antioxidant potential. Characterization of these compounds is necessary to understand the chemical profile of the crystal guava fruit, especially in the edible portion. The objective of this study was to determine the total phenolic and flavonoid profiles in crystal guava fruit pulp extract with different maturation levels. This study was an experimental laboratory-based analytical study. Fruit pulp samples were dried to a constant weight, then extracted using the maceration method with methanol as the solvent. Total phenolic content was determined using the Folin–Ciocalteu method and expressed as gallic acid equivalents, while total flavonoid content was analyzed using the AlCl3 method and expressed as quercetin equivalents. Absorbance measurements were performed using a UV–Vis spectrophotometer. The data were analyzed using the Kruskal–Wallis nonparametric test, followed by the Mann–Whitney test to assess group differences. Results showed that the total flavonoid content from three samples was 130.9 mg QE/g extract, 93.3 mg QE/g extract and 185.9 mg QE/g extract. Meanwhile, total phenolic compound content was 198.5 mg GAE/g extract, 210.4 mg GAE/g extract, and 345.0 mg GAE/g extract. Statistical analysis showed significant differences (p<0.05) in the total phenolic and flavonoid content between extract groups. These findings indicate that crystal guava fruit extract has significant variation in phenolic and flavonoid compound content, making it a potential subject for further study in the context of food-based bioactive compound utilization.